The future of childhood : towards the interdisciplinary study of children - Prout, Alan (RoutledgeFalmer, 2005)
Alan Prout discusses the place of children and childhood in the late modernity. He argues that there appears to be a greater cultural confusion about the form that childhood should take.- Resumé vydavatel
Keywords: děti -- sociální poměry -- 20.-21. století; sociologie dětství -- 20.-21. století; studium a výuka; children -- social conditions -- 20th - 21st centruries; sociology of childhood -- 20th - 21st centruries; study and teaching; elektronické knihy; monografie; electronic books; monographs